Investigating the Effect of Mixed Reality Technology on Enhancing Virtual Tourism Experience (American Journal of Innovation in Science and Engineering, 2025)
This study investigates the impact of Mixed Reality (MR) technology encompassing Augmented Reality (AR) and Virtual Reality (VR) – on enhancing the virtual tourism experience in Cotabato City’s tourist spots. A quantitative research design was employed, using a survey questionnaire to collect data from 70 respondents via random sampling. The questionnaire measured user perceptions across factors derived from technology acceptance and information systems success models: perceived usefulness, perceived ease of use, perceived enjoyment, information quality, system quality, service quality, intention to use, and user satisfaction. The Kutawatu Go MR mobile application, which provides virtual tours of Cotabato City’s attractions, served as the platform for the virtual tourism experience. Descriptive statistics indicated overwhelmingly positive user perceptions on all measured aspects, with mean ratings mostly in the “Agree” to “Strongly Agree” range on a 5-point Likert scale. Notably, respondents found the MR application highly useful (mean ≈4.58/5) and enjoyable (≈4.55/5), and they expressed strong intentions both to continue using the app and to eventually visit the physical sites. The instrument demonstrated excellent reliability (Cronbach’s α = 0.966). Correlation analysis revealed that key user perception factors (e.g. perceived usefulness, enjoyment, and quality dimensions) are strongly and significantly associated with both intention to use the MR system and overall satisfaction (all p < 0.01). These findings suggest that MR technology can greatly enhance user engagement and satisfaction in virtual tourism. The study contributes to the growing body of knowledge on immersive technologies in tourism by empirically validating theoretical models (Technology Acceptance Model and Information Systems Success Model) in a virtual tourism context. It also provides practical insights for tourism stakeholders and policymakers in leveraging MR applications to promote tourist destinations and augment visitor experiences remotely.